MINKPRODUKTION I DANMARK – HØJ RISIKO OG TIL TIDER HØJT AFKAST. - Bramsen, J.; Fredenslund, T.; Schou, J. (Tidsskrift for Landøkonomi, 2024)
MINKPRODUKTION I DANMARK – HØJ RISIKO OG TIL TIDER HØJT AFKAST.